Facebook Posting as Socio-Political Action in Bulgaria’s Quarantine and Social Distancing Contexts - Nelly Tincheva (Slavia Meridionalis, 2025)
Facebook Posting as Socio-Political Action in Bulgaria’s Quarantine and Social Distancing Contexts The paper explores dynamics in Facebook users’ attitudes towards their interaction on the platform before and during the COVID-19 pandemic. It reports on a questionnaire-based study involving 120 respondents from Bulgaria, where Facebook enjoys an atypical 98% of all social media site visits. The investigation registers trends in attitudes to Facebook posting during the quarantine period and during the social-distancing period; these are contrasted with pre-pandemic data. The data reveal that, before the pandemic, Facebook was used socio-politically in order to debate a socio-political issue and to exchange socio-political information. In the quarantine period, people used Facebook primarily to debate a socio-political issue and to motivate others to take socio-political (in)action. In the social-distancing period, people used Facebook primarily to motivate others to take socio-political (in)action and to debate a socio-political issue. Special attention is paid to one of the registered tendencies, namely the steep increase in respondents’ viewing their posting on Facebook as performing actual socio-political action. An explanation is offered as to how online FACEBOOK COMMUNICATION comes to be conceptualized as offline ACTION.   Postowanie na Facebooku jako akcja społeczno-polityczna w kontekście kwarantanny i dystansowania społecznego w Bułgarii Artykuł bada dynamikę zmian postaw użytkowników Facebooka wobec ich interakcji na platformie przed i w trakcie pandemii COVID-19. Opisuje badanie oparte na ankiecie, w którym wzięło udział 120 respondentów z Bułgarii, gdzie Facebook cieszy się nietypową popularnością, obejmującą 98% wszystkich wizyt na stronach mediów społecznościowych. Badanie rejestruje trendy w postawach wobec postowania na Facebooku w czasie kwarantanny oraz okresu dystansowania społecznego, które są porównane z danymi sprzed pandemii. Wyniki pokazują, że przed pandemią Facebook był wykorzystywany w celach społeczno-politycznych do debaty nad kwestiami społeczno-politycznymi oraz wymiany informacji społeczno-politycznych. W okresie kwarantanny ludzie używali Facebooka głównie do debatowania nad kwestiami społeczno-politycznymi oraz motywowania innych do podejmowania społeczno-politycznych działań (lub ich braku). W okresie dystansowania społecznego użytkownicy Facebooka wykorzystywali platformę głównie do motywowania innych do podejmowania działań (lub ich braku) oraz do debatowania nad kwestiami społeczno-politycznymi. Szczególna uwaga została poświęcona jednej z zauważonych tendencji, a mianowicie gwałtownemu wzrostowi liczby respondentów postrzegających swoje postowanie na Facebooku jako faktyczne działanie społeczno-polityczne. Zaproponowano wyjaśnienie sytuacji, w jaki sposób komunikacja online na Facebooku zaczyna być postrzegana jako działanie offline.